English in economics and business : - Bales, Sarah (Giao duc, 1998)
Contents: chapter 1: the market economy, Chapter 2: history, chapter 3: macroeconomics, chapter 4: microeconomics, chapter 5: international economics, chapter 6: inflation, chapter 7: labor, chapter 8: demography, chapter 9: investments